(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bacterial concrete is one of the methods of rectifying the micro-cracks developed in the structural elements made of concrete. The gram-positive type bacteria Bacillus subtilis when acquainted with concrete produces calcite precipitation which heals the micro cracks in the concrete. Bacillus subtilis was used with a cell concentration of 106. The optimised percentage replacement of fine aggregates with sugarcane fibres of grain size less than 4.75 mm was 0.1 %. The effect of sugarcane fibres on the durability of bacterial concrete is presented in this paper.To study the Stress -Strain behaviour of Sugarcane based Bacterial concrete (SBC), appropriate analytic SS model is developed that resembles the experimental behaviour of the various samples such as Conventional Concrete (CC), Bacterial Concrete (BC) and SBC. This work mainly targets on utilizing the earlier models and offers a new SS model that can well represent the actual SS behaviour of SBC samples. After finding the SS behaviour of CC, BC and SBC specimens experimentally, equations are developed to characterise axial SS behaviour of CC, BC and SBC samples. From these mathematical equations, theoretical stress for CC, BC and SBC are calculated and compared with test values. The proposed equations have exposed good connection with test values authorizing the mathematical model developed.